2009
DOI: 10.2190/hs.39.3.e
|View full text |Cite
|
Sign up to set email alerts
|

Policies to Tackle Health Inequalities in Norway: From Laggard to Pioneer?

Abstract: This study addresses recent public health policies in Norway, asking how policies on health inequalities have developed over the past 20 years. The authors focus on how the problem has been defined, what goals have been set, and what means have been put forward to achieve them. The data consist of official documents and interviews of key actors in research and the health bureaucracy. The results indicate that the theme of health inequalities has developed from a non-topic to a high-priority topic in Norway's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…For example, Dahl describes the emergence of priority for SDHI in Norway alongside the election of a new government and a corresponding shift in the problem definition from “individualization with a focus on health behaviours” to a “structural understanding that emphasizes the problem of the gradient and the SDH” (p. 509). 32 In others, framing of target groups was viewed as problematic. For example, in Australia, Aboriginal and Torres Strait Islander peoples were often framed as irresponsible and incompetent at managing their health, with an underlying frame of ‘otherness.’ 28 Imagery and stories about ‘remote communities’ (ie, as distant from mainstream urban Australians) and a disproportionate use of an ‘Indigenous health crisis’ frame were used to support a conservative Government’s radical Indigenous affairs agenda.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Dahl describes the emergence of priority for SDHI in Norway alongside the election of a new government and a corresponding shift in the problem definition from “individualization with a focus on health behaviours” to a “structural understanding that emphasizes the problem of the gradient and the SDH” (p. 509). 32 In others, framing of target groups was viewed as problematic. For example, in Australia, Aboriginal and Torres Strait Islander peoples were often framed as irresponsible and incompetent at managing their health, with an underlying frame of ‘otherness.’ 28 Imagery and stories about ‘remote communities’ (ie, as distant from mainstream urban Australians) and a disproportionate use of an ‘Indigenous health crisis’ frame were used to support a conservative Government’s radical Indigenous affairs agenda.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Norway external technical publications (eg, the Black Report in the United Kingdom and WHO reports) were seen as driving a domestic research agenda, and subsequently new Norwegian data and evidence sparked public attention. 32 Data on disparities in the health status of Aboriginal and Torres Strait Islander people was found to be an important driver of increased funding and priority for Indigenous health research. 36 Comparative data demonstrating differences in health inequalities between national-, 32 and among local-level, 38 jurisdictions was found to be compelling to decision-makers in some studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dahl () found that key values that supported the goal of reducing inequalities were social justice and the view that it was a community responsibility to ensure fair distribution of health services. Norwegian health policy emphasizes health promotion through improved living conditions, universal services that are not tied to one's position in the labor market, and fair distribution of resources through reducing the social inequalities that contribute to health inequalities (Fosse, ).…”
Section: Introductionmentioning
confidence: 99%